1991
DOI: 10.1128/jb.173.18.5887-5892.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the gene (ard) encoding the antirestriction protein of plasmid colIb-P9

Abstract: The IncIl plasmid ColIb-P9 was found to encode an antirestriction function. The relevant gene, ard (alleviation of restriction of DNA), maps about 5 kb from the origin of transfer, in the region transferred early during bacterial conjugation. Ard inhibits both restriction and modification by each of the four type I systems of Escherichia coli tested, but it had no effect on restriction by either EcoRI, a type II system, or EcoPl, a type III system. The nucleotide sequence of the ColIb ard gene was determined; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
0
45
2
Order By: Relevance
“…ArdB is encoded by the leading region of pKM101 that is transferred early during conjugation and has been shown to possess an antirestriction activity directed primarily against type I restriction endonucleases (7). Like ArdB, the predicted KlcA polypeptide shows no significant similarity to other known proteins with antirestriction activity (ArdA of pKM101 [6], Ard of ColIb-P9 [11,46], and the product of the 0.3 gene of bacteriophage T7 [13]). The regulation of ardB is strikingly similar to the regulation of kicA.…”
Section: Methodsmentioning
confidence: 99%
“…ArdB is encoded by the leading region of pKM101 that is transferred early during conjugation and has been shown to possess an antirestriction activity directed primarily against type I restriction endonucleases (7). Like ArdB, the predicted KlcA polypeptide shows no significant similarity to other known proteins with antirestriction activity (ArdA of pKM101 [6], Ard of ColIb-P9 [11,46], and the product of the 0.3 gene of bacteriophage T7 [13]). The regulation of ardB is strikingly similar to the regulation of kicA.…”
Section: Methodsmentioning
confidence: 99%
“…It was built the M.EcoKI-ArdA model: domain 3 overlaps the EcoKI target sequence, domain 2 contacts the extremites of the DNA-binding groove in M.EcoKI and domain 3 projects beyond the M.EcoKI structure. Domain 1 is not essential for antirestriction as it can be deleted (Delver et al, 1991) indicating that the key aspect of antirestriction by ArdA is the binding to the MTase core using domains 2 and 3.…”
Section: Dna Mimicry By Antirestriction Proteinsmentioning
confidence: 99%
“…An investigation of antirestriction mechanisms employed by transmissible plasmids showed that the process involves a specialized antirestriction protein encoded by the ardA gene (alleviation of restriction of DNA). ardA genes were first discovered in plasmids of the incompatibility group N in 1984-1985(Belogurov et al,1985, and later in other types of plasmids (Kotova et al, 1988;Delver et al, 1991). In 1991-1995, ardA genes were sequenced and the primary structure of ArdA proteins was determined (Delver et al, 1991;Chilley & Wilkins, 1995).…”
Section: Conjugative Plasmids and Transposons Bacteriophages And Anmentioning
confidence: 99%
See 1 more Smart Citation
“…from promoters active in single-stranded DNA. This region includes an anti-restriction gene such as ardA (Delver et al, 1991 ;Read et al, 1992 ;Belogurov et al, 1993 ; Retrotransfer and gene capture Chilley & Wilkins, 1995) and an inhibitor of the bacterial SOS response such as psiB Golub et al, 1988 ;Bagdasarian et al, 1992). Some properties of the ArdA system are identified from the cross-protection of the IncPβ R751 by a co-transferring ColIb.…”
Section: Conjugativementioning
confidence: 99%